(untitled) - Ackert, Patricia (Boston, MA, 1994)
This book offers challenging and entertaining readings of gradually increasing length and complexity, presented within a carefully controlled system of vocabulary. New to the second edition: prereading activities new readings on new topics, and postreading writing exercises
Keywords: english language - textbooks for foreign speakers